The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s13550-021-00803-9
|View full text |Cite
|
Sign up to set email alerts
|

Competitive blocking of salivary gland [18F]DCFPyL uptake via localized, retrograde ductal injection of non-radioactive DCFPyL: a preclinical study

Abstract: Background PSMA-targeted radionuclide therapy (TRT) is a promising treatment for prostate cancer (PCa), but dose-limiting xerostomia can severely limit its clinical adaptation, especially when using alpha-emitting radionuclides. With [18F]DCFPyL as a surrogate for PSMA-TRT, we report a novel method to selectively reduce salivary gland (SG) uptake of systemically administered [18F]DCFPyL by immediate prior infusion of non-radioactive standard of [18F]DCFPyL (DCFPyL) directly into the SG via retr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…However, adding the albumin-binding motif to the bivalent ligand impaired its PSMA binding capability, with the IC 50 of DOTA-Alb-Bi-PSMA reduced to 8.68 ± 3.10 nM. , All PSMA ligands were radiolabeled with gallium-68 and lutetium-177 and exhibited good stability in PBS and human serum. It has been reported that self-blocking of PSMA ligands can significantly affect the distribution of the radioligands in vivo; , therefore, in this study, the 177 Lu-labeled ligands were purified by HPLC for further study.…”
Section: Discussionmentioning
confidence: 99%
“…However, adding the albumin-binding motif to the bivalent ligand impaired its PSMA binding capability, with the IC 50 of DOTA-Alb-Bi-PSMA reduced to 8.68 ± 3.10 nM. , All PSMA ligands were radiolabeled with gallium-68 and lutetium-177 and exhibited good stability in PBS and human serum. It has been reported that self-blocking of PSMA ligands can significantly affect the distribution of the radioligands in vivo; , therefore, in this study, the 177 Lu-labeled ligands were purified by HPLC for further study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, long-term salivary gland toxicity needs to be investigated. A recent pilot study investigated the use of cold DCFPyL instillation into the salivary glands in order to decrease salivary uptake, mitigating xerostomia in patients scheduled for radioligand therapy [178]. Numerous studies have recently evaluated the application of Cu as PET/TC radiotracer in oncology because of its capacity to act as diagnostic and theragnostic radiotracer.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…A recent preclinical study also reported on direct retrograde installation of the nonradioactive standard of [ 18 F]DCFPyL, that is DCFPyL, into the salivary glands, potentially decreasing salivary uptake. Such blocking experiments may pave the way to mitigate xerostomia in a clinical setting, e. g., in patients scheduled for RLT [55]. Last, in patients scheduled for RLT, PET/CT-based parameters at baseline may predict early biochemical response and overall survival [56,57].…”
Section: Future Perspectivesmentioning
confidence: 99%